2017
DOI: 10.4049/jimmunol.1600802
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD83 Inhibits T Cell Activation by Binding to the TLR4/MD-2 Complex on CD14+ Monocytes

Abstract: The transmembrane protein CD83, expressed on APCs, B cells, and T cells, can be expressed as a soluble form generated by alternative splice variants and/or by shedding. Soluble CD83 (sCD83) was shown to be involved in negatively regulating the immune response. sCD83 inhibits T cell proliferation in vitro, supports allograft survival in vivo, prevents corneal transplant rejection, and attenuates the progression and severity of autoimmune diseases and experimental colitis. Although sCD83 binds to human PBMCs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 77 publications
1
44
0
Order By: Relevance
“…The overactive phenotype observed in CD83-cKO DCs is also characterized by increased IRAK1 expression levels, which points toward an enhanced TLR signaling capacity. Interestingly, previous reports demonstrated that sCD83 also alters TLR signaling by binding to MD-2 on human monocytes, resulting in a long-lasting degradation of IRAK1 and subsequent induction of tolerogenic mechanisms (57). Likewise, CD83 on DCs could negatively modulate the TLR pathway either in cis or in trans, which would account for exaggerated inflammatory immune responses in CD83 ΔDC animals.…”
Section: Discussionmentioning
confidence: 98%
“…The overactive phenotype observed in CD83-cKO DCs is also characterized by increased IRAK1 expression levels, which points toward an enhanced TLR signaling capacity. Interestingly, previous reports demonstrated that sCD83 also alters TLR signaling by binding to MD-2 on human monocytes, resulting in a long-lasting degradation of IRAK1 and subsequent induction of tolerogenic mechanisms (57). Likewise, CD83 on DCs could negatively modulate the TLR pathway either in cis or in trans, which would account for exaggerated inflammatory immune responses in CD83 ΔDC animals.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, first insights regarding CD83-mediated signaling events were published (48). This study reported that on monocytes sCD83 binds to the TLR4/MD-2 complex and alters the signaling cascade by rapidly degrading IRAK-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, this self-interaction is not sufficient to explain the regulatory effects of sCD83 on monocytes (68), which -in contrast to DCs -do not express mbCD83 in the steady state (32). Thus, a recent study elucidated the impact of sCD83 on monocytes by demonstrating sCD83 binding to MD-2 and the TLR4 complex (69). The authors suggested that upon binding to MD-2, sCD83 initiates an anti-inflammatory TLR-signaling cascade leading to long-term depletion of IRAK-1, which causes unresponsiveness to further TLR stimulation.…”
Section: Cd83 Binding Partners and Signaling Cascadesmentioning
confidence: 99%